Análisis Termográfico de Reactores Nucleares Basado en el Código RELAP/SCDAP - Sánchez Mora, Heriberto (My University, 2018)
Energía Nuclear,RELAP/SCDAPSIM,OpenGL,CORA-17.
Keywords: Energía Nuclear,RELAP/SCDAPSIM,OpenGL,CORA-17.